2013
DOI: 10.3748/wjg.v19.i17.2718
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of the Qing Dai in patients with intractable ulcerative colitis

Abstract: Ulcerative colitis (UC) is a chronic inflammatory bowel disease that may become intractable when treated with conventional medications such as aminosalicylates, corticosteroids, and azathioprine. The herbal medicine Qing Dai has traditionally been used in Chinese medicine to treat UC patients, but there is a lack of published data on the efficacy of Qing Dai in UC treatment. We report several cases of patients with intractable UC who take Qing Dai in a retrospective observational study. Furthermore, we explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 12 publications
4
77
0
Order By: Relevance
“…2f). We also confirmed the known ability of IND to scavenge reactive oxygen species [1], which can also influence intestinal inflammation by electron spin resonance. Electron spin resonance results revealed a decreased spectrum of hydroxyl radical, superoxide radical, and singlet oxygen with IND treatment (online suppl.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…2f). We also confirmed the known ability of IND to scavenge reactive oxygen species [1], which can also influence intestinal inflammation by electron spin resonance. Electron spin resonance results revealed a decreased spectrum of hydroxyl radical, superoxide radical, and singlet oxygen with IND treatment (online suppl.…”
Section: Resultssupporting
confidence: 65%
“…Increased levels of IL-13 have been proven to exist in the intestines of UC patients [26,37]. Therefore, the amelioration of UC symptoms by IND reported by 2 clinical studies [1,13] may be by this mechanism. Furthermore, we have also confirmed that IND reduces free radicals (online suppl.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These ligands induce the production of interleukin-22 from innate lymphoid cell type 3, which results in the upregulation of the expression of tight junction molecules and antimicrobial peptides to promote mucosal healing [61,62]. Previously, the usefulness of Qing-Dai for UC was reported [63,64]; however, no prospective clinical trial had been conducted. Recently, we conducted a prospective study to confirm the safety and efficacy of Qing-Dai for UC [65].…”
Section: Herbal Medicinementioning
confidence: 99%